2021
DOI: 10.1111/jace.17644
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐friendly Mn‐doped CsPbCl3 perovskite nanocrystal glass with blue‐red emission for indoor plant lighting

Abstract: Mn‐doped CsPbCl3 perovskite nanocrystal (PeNC) glass was prepared by melt quenching and in situ crystallization. Under the protection of robust glass, PeNCs exhibit excellent moisture resistance and thermal stability. The combination effect of thermal quenching and energy transfer of exciton to Mn2+ enables its promising applications in the field of temperature sensor. Interestingly, by matching with ultraviolet chips, all‐inorganic blue‐red emitting conversion device consisting of PeNC glass was prepared for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Therefore, these results further confirmed that the Mn 2+ ions, which partially replaced Pb 2+ sites, had stronger chemical interactions with Cl – than Pb 2+ , partially reducing the interactions between extranuclear and core electrons in these neighboring ions (Pb 2+ and Cl – ) because Mn has lower electronegativity than Pb . The present results corroborated the previous reports on Mn 2+ ion-substituted CsPbCl 3 PNCs. ,, The chemical composition of the Mn-doped CsPbCl 3 was further investigated from the energy-dispersive X-ray spectroscopy (EDS) measurements (Figure f) and atomic composition (pie chart) shown in the inset of Figure f and elemental composition (Figure S2) for a Mn/Pb feed ratio of 2:1. The molar ratio of Cs, Pb, Cl, and Mn in Mn-doped PNCs was 1.0:1.62:5.34:1.02.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, these results further confirmed that the Mn 2+ ions, which partially replaced Pb 2+ sites, had stronger chemical interactions with Cl – than Pb 2+ , partially reducing the interactions between extranuclear and core electrons in these neighboring ions (Pb 2+ and Cl – ) because Mn has lower electronegativity than Pb . The present results corroborated the previous reports on Mn 2+ ion-substituted CsPbCl 3 PNCs. ,, The chemical composition of the Mn-doped CsPbCl 3 was further investigated from the energy-dispersive X-ray spectroscopy (EDS) measurements (Figure f) and atomic composition (pie chart) shown in the inset of Figure f and elemental composition (Figure S2) for a Mn/Pb feed ratio of 2:1. The molar ratio of Cs, Pb, Cl, and Mn in Mn-doped PNCs was 1.0:1.62:5.34:1.02.…”
Section: Resultssupporting
confidence: 90%
“…The survey-scan XPS spectra of pristine and Mn 2+ -doped CsPbCl 3 PNCs (Figure 3a) showed the characteristic peaks of cesium (Cs: 3d), lead (Pb: 4f), chlorine (Cl: 2p), and manganese (Mn: 2p) in the synthesized samples. 19,42,48,49 The carbon (C) peak at approximately 284.8 eV was attributed to the organic ligands oleic acid (OA) and oleylamine (OLM). The narrow-scan high-resolution XPS (HR-XPS) spectra of the Cs 3d core level in Figure 3b exhibited a doublet pair (Cs 3d: 3d 3/2 and 3d 5/2 ) structure due to the spin-orbit splitting for pristine and Mn-doped CsPbCl 3 PNCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the emission color of Mn 2+ ions are sensitive to the surrounding crystal‐field environment as reported 12–15 : the octahedrally coordinated Mn 2+ ions emit orange to red light, while the tetrahedrally coordinated Mn 2+ ions act as green luminescent centers. With the crystallization of GC samples, the crystal field of Mn 2+ sites would be easily changed, leading to the varied emission from red to green, which makes it more difficult to controllably prepare Mn 2+ ‐doped GCs with stable red emission.…”
Section: Introductionmentioning
confidence: 99%